Unusual association between Ornithonyssus bursa (Berlese, 1888) (Mesostigmata: Macronyssidae) and Parabuteo unicinctus (Temminck, 1824) (Accipitriformes: Accipitridae) in Paraíba State, Brazil - Takatsu, Júlia C.; Bassini-Silva, Ricardo; de Moura, Ana Paula; Batista, Aksa I. V.; Dias, Glenison F.; Pereira, Josivania S.; Dowling, Ashley P. G.; Jacinavicius, Fernando (Entomological Communications, 2021)
Ornithonyssus bursa (Berlese, 1888), known as the tropical fowl mite, is a hematophagous mite of domestic and wild birds. This mite can bite humans accidentally, causing “gamasoidosis,” “avian-mite dermatitis,” or “bird-mite dermatitis” in tropical and subtropical regions of the world. In Brazil, O. bursa was previously recorded parasitizing birds of the orders Charadriiformes Huxley, 1867, Columbiformes Latham, 1790, Galliformes Temminck, 1820, Passeriformes Linnaeus, 1758, Strigiformes Wagler, 1830, and Tinamiformes Huxley, 1872. Here, we provide a new association of O. bursa with Harris’s hawk, Parabuteo unicinctus (Temminck, 1824) (Accipitriformes: Accipitridae) and the first record of this mite species in the Paraíba State, Brazil.